Earthquake Disaster Management Preparedness Analysis at Anutapura Regional Hospital Palu City - Napirah, Muhammad Ryman; Vidyanto, Vidyanto; Aulia, Rizkha Putri; Salmawati, Lusia; Munari, Munari (Poltekkes Kemenkes Palu, 2024)
The problem found at Anutapura Regional Hospital is that earthquake disaster preparedness is not yet effective due to the hospital's occupational health and safety organizational structure not being updated since 2020 and lack of special training for the team to deal with earthquake disasters. This qualitative case study aims to analyze the organization, mobilization and activation of human resources in earthquake disaster preparedness at Anutapura Regional Hospital, Palu City. In-depth interviews and observations were conducted with key informants including the hospital director, emergency/disaster preparedness coordinator, and secretary of the occupational health and safety team. The results showed that the organizational structure has been updated in 2023 with defined roles and responsibilities, but monitoring and evaluation mechanisms need improvement to ensure teamwork efficiency and effectiveness. The hospital is constrained in training the team, with no special training available for earthquake disasters, although some internal training has been conducted. Personnel selection is based on competencies aligned with emergency response tasks, focusing on managerial expertise and emergency certification. However, the team is not yet independent with members from various units, resulting in suboptimal implementation. The placement process follows general procedures without special assignments for emergencies, and performance evaluations are not conducted regularly. Anutapura Regional Hospital should implement a special training program that includes earthquake disaster management strategies to enhance preparedness.